2010
DOI: 10.1007/s00200-010-0137-x
|View full text |Cite
|
Sign up to set email alerts
|

On necessary and sufficient conditions for differential flatness

Abstract: This paper is devoted to the characterization of differentially flat nonlinear systems in implicit representation, after elimination of the input variables, in the differential geometric framework of manifolds of jets of infinite order. We extend the notion of Lie-Bäcklund equivalence, introduced in [20], to this implicit context and focus attention on Lie-Bäcklund isomorphisms associated to flat systems, called trivializations. They can be locally characterized in terms of polynomial matrices of the indetermi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
124
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 48 publications
1
124
0
4
Order By: Relevance
“…where τ cm is the mechanical input torque, τ cp is the load torque [10] (16) where k t , R cm and k v are motor constants, η cm is a coefficient that denotes the motor's mechanical efficiency. C p is the specific heat capacity of air and W cp is the compressor mass flow rate.…”
Section: Nonlinear Dynamics Of Pem Fuel Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…where τ cm is the mechanical input torque, τ cp is the load torque [10] (16) where k t , R cm and k v are motor constants, η cm is a coefficient that denotes the motor's mechanical efficiency. C p is the specific heat capacity of air and W cp is the compressor mass flow rate.…”
Section: Nonlinear Dynamics Of Pem Fuel Cellsmentioning
confidence: 99%
“…First it is proven that the dynamic model of the fuel cells is a differentially flat one. This means that all its state variables and its control inputs can be expressed as differential functions of a primary variable which is the so-called flat output [14][15][16][17][18]. Differential (linear) independence is another property that holds between the flat output and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Next,the differential flatness properties of this model are proven using as flat output the rotation angle of the motor. Differential flatness means that all state variables and the control input of the system can be expressed as functions of the flat output and its derivatives [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Next it is shown that the system of the nonlinear ODEs is a differentially flat one. This means that all its state variables and the control inputs can be written as differential functions of one single algebraic variable which is the flat output [31][32][33][34][35][36]. Actually, by examining independently each nonlinear ODE it is shown that this stands again for a differentially flat system, for which a virtual control input can be computed as in the case of flatness-based control for the trivial system.…”
Section: Introductionmentioning
confidence: 99%